Hábitos alimentares de crianças menores de dois anos na região metropolitana de Belém-Pa-Brasil. - SOUSA, Douglas Monteiro de (2023)
Objective: the objective of this research was to describe the eating habits of children under 2 years of age in 3 municipalities in the Metropolitan Region of Belém-Pará-Brasil. Methodology: Descriptive-analytical cross-sectional study with application of an online questionnaire via google forms, carried out in 3 municipalities in the metropolitan region of Belém, Pará. The research sample was simple random, consisting of guardians and/or caregivers (over 18 years old), of children under 24 months, which were achieved through sharing a link over the internet. The questions formulated in the survey were based on food consumption markers from the SISVAN platform, plus questions regarding the use of artificial teats (pacifier and/or bottle) and regarding the consumption of regional foods by the child. The variables studied were measured using the Microsoft Excel program and analyzed using the Bioestat 5.3 program. For analytical statistics, the Kruskal-Wallis statistical test was used. An alpha of 5% was adopted as significance. Results: The sample consisted of 221 responses. Of the caregivers (58.37%) were between 18 and 30 years old, (45.70%) were single and (55.66%) had only one child, in addition to (40.72%) having completed high school, and (32.58%) monthly family income of up to a minimum wage. Regarding children, most (56.11%) were male, aged between one and two years (74.21%). It was found that all children from zero to six months were breastfed. However, there was an early supply of other foods, in addition to the consumption of ultra-processed foods by children up to two years old, it was observed in children aged 1 to 2 years that 4.44% already consumed regional foods. As for the use of artificial nipples, there was a predominance in the age group of children between one and two. Conclusion: The research evidenced inadequate feeding practices in the first years of life, demonstrating the importance of health services together with professionals in the dissemination of information about breastfeeding and feeding. This study proved to be of paramount importance, as there are few studies involving the Metropolitan Region of Belém Pará-Brasil.